Health Tourism di Provinsi Kepulauan Riau: Peluang, Tantangan dan Sustainability : Health Tourism in Riau Islands Province: Opportunities, Challenges and Sustainability - Martias, Indra; Pitriyanti , Luh; Daswito, Rinaldi (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2025)
Riau Islands Province (Riau Islands) has great potential in developing the health tourism sector thanks to its strategic location on the Strait of Malacca, rich local culture, and stunning natural beauty. This paper reviews the opportunities and challenges of developing health tourism in the Riau Islands by highlighting medical and wellness tourism elements. Opportunities include geographical advantages, cultural heritage of traditional medicine, and economic potential from increased health tourist arrivals. However, Riau Islands also faces various challenges, such as the need for international standard health facilities, regulations that support investment, global promotion, and environmental sustainability issues. Collaboration between the central and local governments, industry players, and the community is needed to optimise this potential. With the right strategy, the Riau Islands has the opportunity to become a leading health tourism destination in the Asian region.